2019
DOI: 10.1002/cbic.201900455
|View full text |Cite
|
Sign up to set email alerts
|

An Unintentional Discovery of a Fluorogenic DNA Probe for Ribonuclease I

Abstract: Ribonuclease I belongs to a class of nonspecific endoribonucleases and plays many important roles in a variety of biological and cellular processes. While their ubiquitous nature and high activity contribute to the well‐known problem of RNase contamination in experimentation, their abundance in bacteria can potentially be leveraged as a biosensor target. As a result, there is substantial interest in generating a specific and reliable probe for RNase detection for a variety of purposes. To that end, we report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Following a 1 h incubation at room temperature with the CEM of all 26 bacteria, LP1F3′ was cleaved by 10 species within 6 different genus of proteobacteria including: L. pneumophila (L.p; 95 %), Escherichia coli K12 (E.ck; 96 %), Salmonella enterica (S.e; 96 %), Enterobacter cloacae (E.c; 92 %), Klebsiella aerogenes (K.a; 17 %), Shigella sonnei (S.s; 13 %), Shigella flexneri (S.f; 8 %) Klebsiella pneumoniae (K.p; 7 %), Enterobacter aerogenes (E.a; 5 %) , and Ochrobactrum grignonense (O.g; 2 %) ,. Previously our group serendipitously discovered an RFD (RFA13‐1) which was activated by RNase I from several proteobacteria including those listed above, with the exception of L. pneumophila (not tested) and O.gringonese (no activity observed) [34] . Therefore, we hypothesized that the nonspecific cleavage of LP1F3′ observed was most likely due to the presence of RNases, and sought to evaluate the specificity of LP1F3′ in the presence of RNase inhibitors that suppress the activity of RNases (A, B, C, I, and T1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following a 1 h incubation at room temperature with the CEM of all 26 bacteria, LP1F3′ was cleaved by 10 species within 6 different genus of proteobacteria including: L. pneumophila (L.p; 95 %), Escherichia coli K12 (E.ck; 96 %), Salmonella enterica (S.e; 96 %), Enterobacter cloacae (E.c; 92 %), Klebsiella aerogenes (K.a; 17 %), Shigella sonnei (S.s; 13 %), Shigella flexneri (S.f; 8 %) Klebsiella pneumoniae (K.p; 7 %), Enterobacter aerogenes (E.a; 5 %) , and Ochrobactrum grignonense (O.g; 2 %) ,. Previously our group serendipitously discovered an RFD (RFA13‐1) which was activated by RNase I from several proteobacteria including those listed above, with the exception of L. pneumophila (not tested) and O.gringonese (no activity observed) [34] . Therefore, we hypothesized that the nonspecific cleavage of LP1F3′ observed was most likely due to the presence of RNases, and sought to evaluate the specificity of LP1F3′ in the presence of RNase inhibitors that suppress the activity of RNases (A, B, C, I, and T1).…”
Section: Resultsmentioning
confidence: 99%
“…Since RNase T1 is af ungal ribonuclease that is not expressed by bacteria, it cannot be responsible for inducing the observed non-specific cleavage, leaving RNase Iasthe most likely cause.Our conclusion that RNase Ii sl ikely responsible for the observed non-specific cleavage activity is the same conclusion made by the authors for the observed nonspecific cleavage activity of RFA13-1. [34] Furthermore,R Nase Ip rotein sequences corresponding to the 8b acterial species listed previously that were capable of inducing cleavage share high sequence identity. [34] These species express similar RNase Ithat can both nonspecifically cleave LP1F3' and be inhibited by the addition of the SUPERase-In RNase inhibitor.…”
Section: Angewandte Chemiementioning
confidence: 92%
See 2 more Smart Citations
“…serendipitously discovered an RFD (RFA13-1) which was activated by RNase If rom several proteobacteria including those listed above,with the exception of L. pneumophila (not tested) and O.gringonese (no activity observed). [34] Therefore, we hypothesized that the nonspecific cleavage of LP1F3' observed was most likely due to the presence of RNases,and sought to evaluate the specificity of LP1F3' in the presence of RNase inhibitors that suppress the activity of RNases (A, B, C, I, and T1). By process of elimination, it was found that RNase Ii sl ikely responsible for the nonspecific cleavage activity exhibited by LP1F3',g iven that nonspecific cleavage was observed in the presence of an RNase A, Ba nd C inhibitor (NxGen RNase inhibitor), but not observed when an RNase A, B, C, Ia nd T1 inhibitor (SUPERase-In RNase inhibitor) was used ( Figure 3C).…”
Section: Research Articlesmentioning
confidence: 99%